2021
DOI: 10.1101/2021.11.01.21265757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liquid-biopsy transcriptomic profiling uncovers molecular mediators of resistance to androgen receptor signaling inhibition in lethal prostate cancer

Abstract: Androgen receptor signaling inhibitors (ARSi) are a mainstay for patients with metastatic castration-resistant prostate cancer (mCRPC). However, patient response is heterogeneous and the molecular underpinnings of ARSi resistance are not well elucidated. Here we performed transcriptome analysis of circulating tumor cells (CTCs) and peripheral blood mononuclear cells (PBMC) in the context of a prospective clinical trial of men with mCRPC treated with abiraterone (Abi) or enzalutamide (Enza). CTC RNA-sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…CTCs were enriched via negative depletion of CD45 + -cells and labeled live with antibodies against the cell surface proteins, TfR, EpCAM and CD45 ( Supplementary Figure 4A ). In a different cohort of mCRPC, we recently used the same enrichment protocol and established the prostate cancer origin of CTCs using a stringent transcriptomic pipeline ( 9 ). In the current cohort of 32 mCRPC patients, CTCs were enumerated based on their respective immunophenotypes as TfR + /EpCAM - /CD45 - (hereafter TfR + ), EpCAM + /TfR - /CD45 - (hereafter EpCAM + ) and TfR + /EpCAM + /CD45 - (double positive).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCs were enriched via negative depletion of CD45 + -cells and labeled live with antibodies against the cell surface proteins, TfR, EpCAM and CD45 ( Supplementary Figure 4A ). In a different cohort of mCRPC, we recently used the same enrichment protocol and established the prostate cancer origin of CTCs using a stringent transcriptomic pipeline ( 9 ). In the current cohort of 32 mCRPC patients, CTCs were enumerated based on their respective immunophenotypes as TfR + /EpCAM - /CD45 - (hereafter TfR + ), EpCAM + /TfR - /CD45 - (hereafter EpCAM + ) and TfR + /EpCAM + /CD45 - (double positive).…”
Section: Resultsmentioning
confidence: 99%
“…As CTCs represent tumor cells with intact DNA, RNA and protein content, unlike the fragmented cfDNA, they can provide comprehensive information about the tumors they disseminate from, which can be used in precision oncology. For example, we and others have demonstrated that transcriptomic CTC profiling can identify gene signatures predictive of clinical response to standard of care treatments ( 8, 9 ). However, such a treatment customization approach has not been clinically adopted due to the lack of a uniform CTC isolation platform.…”
Section: Introductionmentioning
confidence: 99%